Narrative practices in developing professional identities: Issues of objectivity and agency (UCL Press, 2021)
This article presents an analytical model of binary dimensions of narrative practice perceived as two continua between the oppositions of subjectivity/objectivity and structure/agency. Such narrative practice is considered as a site for professional 'identification' and self-knowing. The analytical model provided a framework that was applied to a series of professional life history narrative events and follow-up discussions conducted with six early career teacher educators working across two contrasting sites for teacher education. The findings evidence participants' reflections within the narrative events that relate to the descriptors of each quadrant in this model and show that it has utility in describing and understanding the process of identification that takes place within narrative practice.